Mustahik Empowerment Through Lazismu Family Economic Business Development Program In Parepare - Sarni Fatma Yuna; Moh. Yasin Soumena; St. Nurhayati (Department Of Management Zakat and Waqf, 2023)
This study aims to determine the form of the Family Economic Business Development program (BUEKA), to determine the factors that affect mustahik empowerment through the Family Economic Business Development program (BUEKA), and to discover the implications of the Family Economic Business Development program (BUEKA) in mustahik empowerment. This research uses a qualitative approach and collects data using field research methods (Field Research). The data sources used in this study are primary and secondary data sources, the data collection methods used are interviews and documentation. The results show that, 1) The form of the BUEKA work program is: knowing the feasibility of mustahik, analyzing mustahik needs, achieving administrative requirements, providing capital based on business scale, mustahik religious guidance and reporting business results. 2) Factors that affect mustahik empowerment through the BUEKA program are: proper capital management, accuracy in choosing locations and businesses, entrepreneurial motivation, and products sold needed by the surrounding community 3) Implications of the Family Economic Business Development program in mustahik empowerment, namely: mustahik can open a business, mustahik can continue its business, mustahik needs can be met and has realized human values.